Inhibition mechanism of the radical inhibitors to alkaline degradation of anion exchange membranes. (July 2018) - Ye, Niya; Xu, Yixin; Zhang, Dengji; Yang, Jingshuai; He, Ronghuan
Abstract: We employed four radical inhibitors to investigate their influences on the degradation of poly (4-vinylbenzyl chloride-styrene) based anion exchange membranes (AEMs) in alkaline solutions. It is found that the presence of the radical inhibitors could effectively restrain the nucleophilic attack of hydroxide ions to the AEMs according to the conductivity measurements, especially the one p -ethyl phenol (PEP), which could significantly protect the AEMs against the attack. More evidences including water uptake, swelling ratio as well as FT-IR analysis further proved this phenomenon by comparison those properties of the membranes before and after the stability test in 8 M KOH at 80 °C for 24 h. According to the 1 H NMR spectra, the quaternary ammonium groups of the AEMs were mainly degraded into tertiary amines in the hot alkaline solutions; while in the presence of PEP, this degradation was restrained and the quaternary ammonium groups maintained by reaction with PEP. Fenton test results further indicated that high oxidative stability of the AEMs benefited from the presence of a small amount of PEP, which could reduce the generation of the oxidants. Thus an inhibition reaction mechanism of the radical inhibitors preventing the AEMs from alkaline degradation is proposed. Highlights: Radical inhibitors are verified to restrain the alkaline degradation of AEMs. It is proved that p -ethyl phenol can consume radicals and react with polymers. The mechanism of inhibitors protecting the AEMs from the nucleophilic attack.